Exploration of the Role of Real Context in Developing Mathematical Understanding Through the Realistic Mathematics Education Approach - Dian Krissila Setioningsih; Imas Srinana Wardani; Prayogo Prayogo (Newinera Publisher, 2025)
This study explores the role of real-world contexts in developing students’ mathematical understanding through the Realistic Mathematics Education (RME) approach at Gunung Sekar Elementary School, Sampang. The background of this research lies in the low mathematical comprehension of elementary students, largely due to abstract, teacher-centered instruction. Using a qualitative exploratory case study, data were collected through classroom observations, interviews, and documentation involving 25 sixth-grade students, with six selected for in-depth analysis. The findings revealed that implementing RME by introducing contextual problems such as daily life situations involving division, measurement, and fractions significantly enhanced students’ conceptual understanding, engagement, and confidence in mathematics learning. Students demonstrated improvements in explaining concepts, using multiple representations, and applying mathematical ideas to new contexts. Moreover, the learning process promoted active participation, collaboration, and critical thinking. Teachers transitioned from information providers to facilitators who guided exploration and reflection. The study concludes that the integration of real contexts within RME makes abstract concepts more meaningful and accessible to students, thereby improving both cognitive and affective learning outcomes. These results emphasize the potential of RME as an effective pedagogical strategy to strengthen mathematical literacy and cultivate positive attitudes toward mathematics in Indonesian elementary education.